Mediation effect of maternal triglyceride and fasting glucose level on the relationship between maternal overweight/ obesity and fetal growth: a prospective cohort study - Yanmei Wan; Yixuan Chen; Xiaoxia Wu; Aiqi Yin; Fuying Tian; Huafan Zhang; Xuna Huang; Linlin Wu; Jianmin Niu (BMC Pregnancy and Childbirth, 2023)
Abstract Background Previous studies have suggested that maternal overweight/obesity is asscociated with macrosomia. The present study aimed to investigate the mediation effects of fasting plasma glucose (FPG) and maternal triglyceride (mTG) in the relationship between maternal overweight/obesity and large for gestational age (LGA) among non-diabetes pregnant women. Methods This prospective cohort study was conducted in Shenzhen from 2017 to 2021. A total of 19,104 singleton term non-diabetic pregnancies were enrolled form a birth cohort study. FPG and mTG were measured at 24–28 weeks. We analyzed the association of maternal prepregancy overweight/obesity with LGA and mediation effects of FPG and mTG. Multivariable logistic regression analysis and serial multiple mediation analysis were performed. The odds ratio (OR) and 95% confidence intervals (CIs) were calculated. Results Mothers who were overweight or obese had higher odds of giving birth to LGA after adjusting potential confounders (OR:1.88, 95%CI: 1.60–2.21; OR:2.72, 95%CI: 1.93–3.84, respectively). The serial multiple mediation analysis found prepregnancy overweight can not only have a direct positive effect on LGA (effect = 0.043, 95% CI: 0.028–0.058), but also have an indirect effect on the LGA through two paths: the independent mediating role of FPG (effect = 0.004, 95% CI: 0.002–0.005); the independent mediating role of mTG (effect = 0.003,95% CI: 0.002–0.005). The chain mediating role of FPG and mTG has no indirect effect. The estimated proportions mediated by FPG and mTG were 7.8% and 5.9%. Besides, the prepregnancy obesity also has a direct effect on LGA (effect = 0.076; 95%CI: 0.037–0.118) and an indirect effect on LGA through three paths: the independent mediating role of FPG (effect = 0.006; 95%CI: 0.004–0.009); the independent mediating role of mTG (effect = 0.006; 95%CI: 0.003–0.008), and the chain mediating role of FPG and mTG (effect = 0.001; 95%CI: 0.000-0.001). The estimated proportions were 6.7%, 6.7%, and 1.1%, respectively. Conclusion This study found that in nondiabetic women, maternal overweight/obesity was associated with the occurence of LGA, and this positive association was partly mediated by FPG and mTG, suggesting that FPG and mTG in overweight/obese nondiabetic mothers deserve the attention of clinicians.